A method for preparing a positive electrode for a lithium-sulfur battery with a composite solid-phase conversion mechanism and its application
By adopting a composite solid phase conversion mechanism in the positive electrode of the lithium sulfur battery, sulfur is closed in the honeycomb microporous nanocavity and a low-impedance SEI film is generated, which solves the performance defects caused by the polysulfide conversion process in the lithium sulfur battery, and achieves efficient sulfur utilization and battery performance improvement.
Patent Information
- Application Number
- CN202411775097.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-05
AI Technical Summary
Lithium sulfur batteries undergo a "solid-liquid-solid" conversion process in liquid electrolytes, resulting in defects such as low sulfur utilization, slow reaction kinetics and fast capacity decay.
Using a composite solid phase conversion mechanism, the formation and dissolution of polysulfide intermediates are avoided by blocking sulfur in a honeycomb microporous nanocavity and generating a solid electrolyte interface (SEI) film with low impedance and solid strength in the electrolyte solution.
Significantly extend the cycle life of the battery under high sulfur content and low electrolyte/sulfur conditions, greatly improving the performance of lithium-sulfur batteries, including improving specific capacity and cycle stability.
Smart Images

Figure CN119275243B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparing positive electrodes of lithium-sulfur batteries, and in particular relates to a preparation method and application of positive electrodes of lithium-sulfur batteries with a composite solid-phase conversion mechanism. Background Art
[0002] With the rapid increase in demand for electric devices, commercial lithium-ion batteries are approaching the limits of their theoretical capacity and energy density. In recent years, lithium-sulfur batteries have been widely regarded as one of the most promising new generation energy storage devices due to their ideal characteristics of theoretical capacity (1675mAh / g) and energy density (2600 Wh / kg), as well as significant advantages such as cost-effectiveness and environmental friendliness. Despite this, the commercial development of lithium-sulfur batteries still faces challenges. The most significant problem is the serious shuttling behavior caused by the dissolution of polysulfides in liquid electrolytes undergoing a "solid-liquid-solid" transformation process, which leads to defects such as low sulfur utilization, slow reaction kinetics and rapid capacity decay in lithium-sulfur batteries. Although various strategies have been proposed to partially capture polysulfides, the diffusion and migration of polysulfides cannot be completely eliminated due to the mechanism of repeated "solid-liquid-solid" phase conversion, so it is urgent to explore new phase conversion mechanisms.
[0003] The Chinese patent document with publication number CN116936736A discloses embedding sulfur molecules into the internal micropores of a porous carbon matrix, completely avoiding the generation of liquid-phase polysulfides and improving the coulombic efficiency and cycle stability of the battery, but its disadvantage of low sulfur content limits the overall specific capacity of the composite sulfur positive electrode; the Chinese patent document with publication number CN115732668A discloses forming a solid electrolyte interface (SEI) on the surface of the S / C composite material, which can avoid direct contact between the sulfur in the carbon matrix and the electrolyte solution, thereby driving the redox reaction of sulfur in the form of solid-phase conversion. However, ordinary carbon composites cannot achieve a reversible specific capacity of >1000mAh / g under high sulfur loading and low electrolyte / sulfur (E / S) conditions. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a positive electrode of a lithium-sulfur battery with a composite solid-phase conversion mechanism and its application. The positive electrode of the lithium-sulfur battery with a composite solid-phase conversion mechanism not only seals sulfur in a honeycomb microporous nanochamber, but also the catalytic components therein can generate a low-impedance and strong SEI film with the electrolyte. The synergistic effect of the two avoids the formation and dissolution of polysulfide intermediates, thereby significantly extending the cycle life of the battery under high sulfur content and low E / S conditions, and greatly improving the performance of the lithium-sulfur battery under the solid-phase conversion mechanism.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides a method for preparing a positive electrode of a lithium-sulfur battery with a composite solid-phase conversion mechanism, characterized in that it comprises the following steps:
[0006] (1) mixing molybdenum salt, nickel salt and thiourea and dissolving them in water or ethanol to obtain a precursor solution;
[0007] (2) placing carbon nanofibers in a precursor solution for hydrothermal treatment, taking out the treated carbon nanofibers, washing them with a cleaning agent and drying them to obtain a precursor;
[0008] (3) calcining the precursor under a protective atmosphere at a temperature of 500 to 900° C. to obtain a lithium-sulfur battery positive electrode material with a solid phase conversion mechanism;
[0009] (4) mixing the obtained solid phase conversion mechanism lithium-sulfur battery positive electrode material with sulfur powder to melt sulfur to obtain a sulfur positive electrode active material;
[0010] (5) mixing the sulfur positive electrode active material, the conductive agent and the PVDF obtained in step (4) to form a slurry, coating the slurry on the current collector, and drying the slurry to obtain a lithium-sulfur battery positive electrode with a solid phase conversion mechanism;
[0011] (6) The positive electrode, negative electrode, separator, spring sheet, gasket, positive and negative electrode shells and carbonate-based electrolyte of the lithium-sulfur battery with solid phase conversion mechanism obtained in step (5) are assembled into a lithium-sulfur battery, and the battery is initially cycled for 1 to 3 times to form a SEI film on the surface of the positive electrode to obtain a positive electrode of a lithium-sulfur battery with a composite solid phase conversion mechanism.
[0012] Preferably, in step (1), the molybdenum salt is ammonium molybdate or sodium molybdate, and the nickel salt is one of nickel chloride, nickel nitrate or nickel acetate; the molar concentration of the molybdenum salt in the precursor solution is 0.01 to 1 mol / L, the molar ratio of the molybdenum salt to the nickel salt is 1:1 to 50, and the molar ratio of the molybdenum salt to the thiourea is 1:3 to 10.
[0013] Preferably, in step (2), the hydrothermal treatment temperature is 150-300° C., and the time is 6-12 h; the cleaning agent is water or ethanol; and the drying temperature is 60-80° C., and the time is 4-6 h.
[0014] Preferably, in step (3), the protective atmosphere is nitrogen or argon, the heating rate is 2 to 5° C. / min, and the calcination time is 3 to 6 h.
[0015] Preferably, in step (4), the sulfur content in the sulfur positive electrode active material is 30 to 90 wt %, the temperature of the molten sulfur is 155 to 300° C., and the time is 8 to 12 h.
[0016] Preferably, in step (5), the mass ratio of the sulfur positive electrode active material, the conductive agent and PVDF is 7-9:1-2:1, the conductive agent is one of Ketjen black, SuperP and acetylene black, and the coating thickness is 100 μm to 300 μm.
[0017] Preferably, in step (6), the carbonate-based electrolyte is two of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, and propylene carbonate, with a volume ratio of 1-2:1-2; and the cycle voltage range is 0.01-1V.
[0018] Preferably, in step (6), the effective components of the positive electrode of the lithium-sulfur battery with a composite solid phase conversion mechanism are mainly composed of a positive electrode material and a SEI film, wherein the positive electrode material is composed of a honeycomb microporous nano-chamber coated with carbon nanofibers formed by a combination of molybdenum disulfide and nickel oxide, the micropore diameter of the positive electrode material is 0.3 to 1 nm, the diameter of the carbon nanofiber is 2.0 to 5 μm, and the molybdenum disulfide is 10.7 to 78.3% of the mass of nickel oxide; the SEI film is composed of a combination of lithium polysulfide, a carbonate-based electrolyte and a composite.
[0019] Another solution provided by the present invention is to apply the lithium-sulfur battery positive electrode with a composite solid-phase conversion mechanism prepared by the above method to a lithium-sulfur battery positive electrode.
[0020] The beneficial effects of the present invention are as follows:
[0021] 1. The present invention prepares a lithium-sulfur battery positive electrode with a composite solid-phase conversion mechanism. First, a lithium-sulfur battery positive electrode material with a solid-phase conversion mechanism is prepared, and sulfur molecules are firmly embedded in a porous carbon matrix, which not only provides sufficient active sites but also facilitates the rapid transmission of electrons and ions; then, the lithium-sulfur battery positive electrode material is mixed with sulfur powder, and the sulfur powder is uniformly dispersed and firmly bonded to the positive electrode material by a melt vulcanization method; then, the obtained sulfur positive electrode active material is mixed and stirred with an appropriate amount of a conductive agent and PVDF, and a slurry is prepared and coated on a current collector to obtain a stable lithium-sulfur battery positive electrode with a solid-phase conversion mechanism; finally, the lithium-sulfur battery positive electrode with a solid-phase conversion mechanism is assembled into a lithium-sulfur battery with a matching suitable electrolyte. Among them, carbonate-based electrolytes have excellent conductivity, a wide voltage range and excellent chemical stability. During the initial cycle, they undergo nucleophilic reactions with lithium polysulfide intermediates and catalytic component complexes to form an SEI film in situ on the surface of the sulfur positive electrode. The SEI film serves as a protective barrier between the electrode material and the electrolyte, eliminating the serious shuttling behavior caused by the "solid-liquid-solid" conversion process.
[0022] 2. The present invention prepares a lithium-sulfur battery positive electrode with a composite solid-phase conversion mechanism. First, in the prepared solid-phase conversion mechanism lithium-sulfur battery positive electrode material, the molybdenum disulfide and nickel oxide complex can react with the carbonate-based electrolyte to form a strong, high lithium ion conductivity and low impedance SEI film, thereby improving the reaction activity of the lithium-sulfur battery under solid-state conversion; in addition, the honeycomb microporous nano-chamber formed by the combination of the molybdenum disulfide and nickel oxide complex has a large internal surface area and abundant microporous channels, which can achieve a high sulfur content; the structure of the honeycomb microporous nano-chamber can provide good mechanical support, reduce the material rupture caused by volume change during the charge and discharge process, thereby improving the structural stability of the battery; during the charge and discharge process, the volume of sulfur will change, and the honeycomb microporous nano-chamber adapts to this volume change by providing a buffer space, reducing the impact on the battery The destruction of the electrode structure; the honeycomb microporous structure may enhance the chemical adsorption capacity of polysulfides, help stabilize the electrode / electrolyte interface, and reduce side reactions; the composite structure of molybdenum disulfide and nickel oxide can provide a continuous electron transmission channel, improve the conductivity and charge and discharge efficiency of the battery; in addition, the micropores have uniformly dispersed molybdenum disulfide and nickel oxide metal sites, which can serve as active centers for catalytic conversion, which is conducive to the rapid conversion of polysulfides to achieve a higher sulfur utilization rate. Therefore, the composite solid-phase conversion mechanism lithium-sulfur battery positive electrode not only seals sulfur in the honeycomb microporous nanochambers, but also the catalytic components therein can form a low-impedance and strong SEI film with the electrolyte. The synergistic effect of the two avoids the formation and dissolution of polysulfide intermediates, and exhibits excellent specific capacity and cycle stability under high sulfur loading and low E / S conditions.
[0023] 3. The composite solid-phase conversion mechanism lithium-sulfur battery positive electrode used in the present invention has an initial specific capacity of 1154.1-1234.6 mAh / g at a charge and discharge rate of 0.2C, and a capacity retention rate of 85.1%-87.8% after 200 cycles of testing. The lithium-sulfur battery positive electrode prepared by the solid-phase conversion mechanism also has an initial specific capacity of only 565.3-886.1 mAh / g at a charge and discharge rate of 0.2C, and a capacity retention rate of only 43.2%-57.5% after 200 cycles of testing. In comparison, the composite solid-phase conversion mechanism lithium-sulfur battery positive electrode prepared by the present invention highlights the superiority of the composite solid-phase conversion mechanism. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The X-ray diffraction (XRD) pattern of the lithium-sulfur battery positive electrode material with solid phase conversion mechanism prepared in Example 1;
[0025] Figure 2 This is a scanning electron microscope (SEM) image of the lithium-sulfur battery positive electrode with a composite solid phase conversion mechanism prepared in Example 1 after cycling;
[0026] Figure 3 This is a transmission electron microscope (TEM) image of the positive electrode of the lithium-sulfur battery with a composite solid-phase conversion mechanism prepared in Example 1 after cycling;
[0027] Figure 4 TEM image of the positive electrode surface of the lithium-sulfur battery with a composite solid phase conversion mechanism prepared in Example 1 after cycling;
[0028] Figure 5 The cycle stability of the lithium-sulfur battery positive electrode with a composite solid phase conversion mechanism prepared in Example 1 at 0.2C;
[0029] Figure 6 It is the electrochemical impedance spectroscopy (EIS) of the positive electrode of the lithium-sulfur battery with the composite solid phase conversion mechanism prepared in Example 1;
[0030] Figure 7 This is the EIS of the positive electrode of the lithium-sulfur battery with a composite solid-phase conversion mechanism prepared in Example 2. DETAILED DESCRIPTION
[0031] The present invention is described in detail below with reference to the embodiments and comparative examples, but the present invention is not limited thereto. Example 1
[0032] (1) ammonium molybdate, nickel nitrate and thiourea are mixed and dissolved in water to obtain a precursor solution; wherein the molar concentration of ammonium molybdate in the precursor solution is 0.5 mol / L, the molar ratio of molybdenum salt to nickel salt is 1:30, and the molar ratio of molybdenum salt to thiourea is 1:5;
[0033] (2) placing carbon nanofibers into a reactor of a precursor solution, hydrothermally treating the carbon nanofibers in an oven at 180°C for 6 hours, taking out the samples from the reactor, washing them with ethanol, and drying them in a drying oven at 60°C for 4 hours to obtain a precursor;
[0034] (3) The precursor was calcined at a heating rate of 2°C / min to 500°C under a nitrogen atmosphere and kept at that temperature for 6 h to obtain a lithium-sulfur battery cathode material (NiO / MoS2@CNFs) with a solid phase conversion mechanism.
[0035] (4) NiO / MoS2@CNFs and sulfur powder were mixed and stirred, and sulfur was melted at 155°C for 10 hours to obtain a sulfur cathode active material (NiO / MoS2@CNFs@S); wherein the sulfur content in the sulfur cathode active material was 70wt%;
[0036] (5) NiO / MoS2@CNFs@S, Ketjen black and PVDF were mixed in a mass ratio of 7:2:1 to form a slurry, which was coated on a current collector to obtain a lithium-sulfur battery positive electrode with a solid phase conversion mechanism; wherein the coating thickness was 200 μm;
[0037] (6) The lithium-sulfur battery positive electrode of the solid phase conversion mechanism, lithium sheet, diaphragm, spring sheet, gasket, positive and negative electrode shell and a mixed solution of dimethyl carbonate and propylene carbonate with a volume ratio of 1:1 were assembled into a lithium-sulfur battery, the E / S ratio was controlled at 7µL / mg, and the battery was initially cycled for 1 cycle at a cycle voltage range of 0.01 to 1V to obtain a composite solid phase conversion mechanism lithium-sulfur battery positive electrode. The micropore diameter was 0.3 to 0.8nm and the diameter of the carbon nanofiber was 2.5 to 4μm measured by SEM and TEM. MoS2 was 33.5% of the mass of NiO measured by inductively coupled atomic emission spectroscopy (ICP-AES). Example 2
[0038] (1) Sodium molybdate, nickel nitrate and thiourea are mixed and dissolved in water to obtain a precursor solution; wherein the molar concentration of ammonium molybdate in the precursor solution is 0.01 mol / L, the molar ratio of molybdenum salt to nickel salt is 1:50, and the molar ratio of molybdenum salt to thiourea is 1:3;
[0039] (2) placing carbon nanofibers into a reactor of a precursor solution, hydrothermally treating the carbon nanofibers in an oven at 150°C for 8 hours, taking out the samples from the reactor, washing them with water, and drying them in a drying oven at 70°C for 5 hours to obtain a precursor;
[0040] (3) The precursor was calcined at 800 °C in an argon atmosphere at a heating rate of 5 °C / min and kept at that temperature for 3 h to obtain NiO / MoS2@CNFs.
[0041] (4) NiO / MoS2@CNFs and sulfur powder were mixed and stirred, and sulfur was melted at 270°C for 8 h to obtain NiO / MoS2@CNFs@S, wherein the sulfur content was 90 wt%;
[0042] (5) NiO / MoS2@CNFs@S, acetylene black and PVDF were mixed in a mass ratio of 7.5:1.5:1 to form a slurry, which was coated on a current collector to obtain a lithium-sulfur battery positive electrode with a solid phase conversion mechanism; wherein the coating thickness was 100 μm;
[0043] (6) The lithium-sulfur battery positive electrode of the solid phase conversion mechanism, lithium sheet, diaphragm, spring sheet, gasket, positive and negative electrode shell and a mixed solution of ethylene carbonate and diethyl carbonate with a volume ratio of 1:2 were assembled into a lithium-sulfur battery, the E / S ratio was controlled at 7µL / mg, and the battery was initially cycled 3 times at a cycle voltage range of 0.01 to 1V to obtain a composite solid phase conversion mechanism lithium-sulfur battery positive electrode. The micropore diameter was 0.3 to 1nm and the diameter of the carbon nanofiber was 3 to 5μm measured by SEM and TEM. MoS2 was 10.7% of the mass of NiO measured by ICP-AES. Example 3
[0044] (1) Sodium molybdate, nickel acetate and thiourea are mixed and dissolved in ethanol to obtain a precursor solution; wherein the molar concentration of ammonium molybdate in the precursor solution is 1 mol / L, the molar ratio of molybdenum salt to nickel salt is 1:25, and the molar ratio of molybdenum salt to thiourea is 1:10;
[0045] (2) placing carbon nanofibers into a reactor of a precursor solution, subjecting them to hydrothermal treatment in an oven at 240°C for 10 h, taking out the sample from the reactor, washing it with water, and drying it in a drying oven at 80°C for 4 h to obtain a precursor;
[0046] (3) The precursor was calcined at a heating rate of 3°C / min to 900°C under a nitrogen atmosphere and kept at that temperature for 4 h to obtain NiO / MoS2@CNFs.
[0047] (4) NiO / MoS2@CNFs and sulfur powder were mixed and stirred, and sulfur was melted at 300°C for 12 hours to obtain NiO / MoS2@CNFs@S; wherein the sulfur content in the sulfur positive electrode active material was 30wt%;
[0048] (5) NiO / MoS2@CNFs@S, Super P and PVDF were mixed in a mass ratio of 7.8:1.2:1 to form a slurry, which was coated on a current collector to obtain a lithium-sulfur battery positive electrode with a solid phase conversion mechanism; wherein the coating thickness was 300 μm;
[0049] (6) The lithium-sulfur battery positive electrode of the solid phase conversion mechanism, lithium sheet, diaphragm, spring sheet, gasket, positive and negative electrode shell and a mixed solution of ethyl methyl carbonate and diethyl carbonate with a volume ratio of 2:1 were assembled into a lithium-sulfur battery, the E / S ratio was controlled at 7µL / mg, and the battery was initially cycled 2 times at a cycle voltage range of 0.01 to 1V to obtain a composite solid phase conversion mechanism lithium-sulfur battery positive electrode. The micropore diameter was 0.5 to 1nm and the diameter of the carbon nanofiber was 2.4 to 4.7μm measured by SEM and TEM. MoS2 was 58.6% of the mass of NiO measured by ICP-AES. Example 4
[0050] (1) ammonium molybdate, nickel chloride and thiourea are mixed and dissolved in ethanol to obtain a precursor solution; wherein the molar concentration of ammonium molybdate in the precursor solution is 0.8 mol / L, the molar ratio of molybdenum salt to nickel salt is 1:1, and the molar ratio of molybdenum salt to thiourea is 1:7;
[0051] (2) placing carbon nanofibers into a reactor of a precursor solution, hydrothermally treating the carbon nanofibers in an oven at 300°C for 12 hours, taking out the sample from the reactor, washing it with ethanol, and drying it in a drying oven at 65°C for 6 hours to obtain a precursor;
[0052] (3) The precursor was calcined at a heating rate of 3°C / min to 600°C under a nitrogen atmosphere and kept at that temperature for 6 h to obtain NiO / MoS2@CNFs;
[0053] (4) NiO / MoS2@CNFs and sulfur powder were mixed and stirred, and sulfur was melted at 200°C for 8 hours to obtain NiO / MoS2@CNFs@S; wherein the sulfur content in the sulfur positive electrode active material was 60wt%;
[0054] (5) NiO / MoS2@CNFs@S, Ketjen black and PVDF were mixed in a mass ratio of 8:1:1 to form a slurry, which was coated on a current collector to obtain a lithium-sulfur battery positive electrode with a solid phase conversion mechanism; wherein the coating thickness was 200 μm;
[0055] (6) The lithium-sulfur battery positive electrode of the solid phase conversion mechanism, lithium sheet, diaphragm, spring sheet, gasket, positive and negative electrode shell and a mixed solution of ethylene carbonate and dimethyl carbonate with a volume ratio of 1:1 were assembled into a lithium-sulfur battery, the E / S ratio was controlled at 7µL / mg, and the battery was initially cycled 3 times at a cycle voltage range of 0.01 to 1V to obtain a composite solid phase conversion mechanism lithium-sulfur battery positive electrode. The micropore diameter was 0.4 to 0.9nm and the diameter of the carbon nanofiber was 2 to 5μm by SEM and TEM measurements. MoS2 was 78.3% of the mass of NiO by ICP-AES. Comparative Example 1
[0056] The electrolyte in this comparative example is 1,3-dioxolane and 1,2-dimethoxyethane in a volume ratio of 1:1. The electrolyte cannot react with the newly generated polysulfide during the first discharge to form a protective SEI film, and the rest is consistent with the process of Example 1. The micropore diameter is 0.3-0.9 nm as measured by SEM and TEM, the diameter of the carbon nanofiber is 2-4 μm, and the MoS2 is 31.9% of the mass of NiO as measured by ICP-AES. Comparative Example 2
[0057] In this comparative example, carbon nanofibers are directly used as the positive electrode material of the lithium-sulfur battery, and the rest of the process is consistent with that of Example 1.
[0058]
[0059] In order to confirm the crystal structure and chemical composition of the prepared materials, we performed XRD on the surface of the cathode materials and the results are shown in Figure 1 According to the XRD spectrum results, in addition to showing a sharp peak belonging to NiO crystals (37.3 o , 43.3 o , 62.9 o , 75.3 oand 79.5 o ), we also observed that at 17.5 o , 32.4 o and 56.3 o Three peaks appeared at , which can correspond to the MoS2 crystal structure. These XRD analysis results further confirmed the presence of NiO and MoS2 in the material.
[0060] Figure 2 This is a SEM morphology of the positive electrode of the composite solid phase conversion mechanism lithium-sulfur battery prepared in Example 1 after cycling. It can be seen from the figure that the positive electrode is composed of a honeycomb microporous nano-chamber composed of a composite of molybdenum disulfide and nickel oxide, which is coated with carbon nanofibers. The diameter of the carbon nanofibers is 2.5 to 4 μm. A thin film is formed on the surface of the positive electrode after multiple cycles. Figure 3 The TEM images in the figure show that the positive electrode of the composite solid-phase conversion mechanism lithium-sulfur battery has a rich microporous structure, and the pore size of these micropores ranges from 0.3 to 0.8 nm. The presence of this microporous structure enables the material to effectively adsorb and store high-sulfur substances. In addition, the micropores also contain uniformly dispersed molybdenum disulfide and nickel oxide metal sites, which act as active centers in the catalytic conversion reaction. The presence of this microporous structure and metal sites can prevent the electrolyte from directly contacting the polysulfides in the material, achieving the occurrence of a solid-phase conversion mechanism, and this solid-phase conversion process enables the polysulfides to be rapidly converted, thereby achieving excellent specific capacity and cycle stability of the material.
[0061] Figure 4 The TEM image in FIG1 shows that the surface of the positive electrode prepared in Example 1 after cycling is covered with a thin and tight SEI film, which indicates that the carbonate-based electrolyte undergoes a nucleophilic reaction with the lithium polysulfide intermediate and the catalytic component to form an SEI film in situ. The SEI film serves as a protective barrier between the electrode material and the electrolyte, eliminating the severe shuttling behavior caused by the "solid-liquid-solid" conversion process, thereby extending the cycle life of the battery and effectively improving the battery performance.
[0062] The electrochemical cycle performance of the lithium-sulfur battery positive electrode of the composite solid phase conversion mechanism prepared in Example 1 was tested at 0.2C for 200 cycles. The specific test results are as follows: Figure 5 As shown. The first discharge capacity of the lithium-sulfur battery cathode prepared in Example 1 reached 1234.6 mAh / g, and after 200 charge and discharge cycles, it still maintained 87.8% of the capacity. The same test was performed on the materials of Examples 2 to 4, and the results were similar to those of Example 1 (Table 1). At a current density of 0.2C, the difference in discharge capacity of the samples of each example did not exceed 80.5 mAh / g, and the difference in capacity retention did not exceed 2.7%.
[0063] Compared with the sample of comparative example 1, Example 1 has a higher discharge specific capacity under 0.2C conditions, and the specific capacity difference with comparative example 1 exceeds 348.0mAh / g, and the difference in capacity retention after 200 cycles is greater than 44.5% (Table 1). These results show that the lithium-sulfur battery of comparative example 1 using a traditional electrolyte mainly follows the "solid-liquid-solid" conversion mode during the charge and discharge process, and the polysulfide is completely dissolved in a large amount of electrolyte, resulting in the occurrence of the shuttle effect, which seriously weakens the performance of the battery. At the same time, the electrolyte reacts adversely with the electrode material, resulting in a poor cycle life of the battery.
[0064] Compared with Comparative Example 2, the higher specific capacity of Example 2 is mainly attributed to the honeycomb microporous nano-chamber composed of the molybdenum disulfide and nickel oxide composite. Specifically, the SEI resistance (R SEI ) and low charge transfer resistance (R CT ) is higher than the characteristic frequency of comparative example 2, and its corresponding R SEI and R CT The relaxation time is shorter ( Figures 6-7 ), which shows that the lithium ion conductivity in the positive electrode SEI film of the lithium-sulfur battery of Example 1 is high and the reaction kinetics are fast. The SEI film has a high conductivity because the molybdenum disulfide and nickel oxide complex reacts with the carbonate-based electrolyte to form a strong, high lithium ion conductivity and low impedance SEI film. For example, the honeycomb microporous nanochambers provide sufficient internal surface area and dense microporous channels, so that sulfur molecules are effectively incorporated into the deep micropores of the porous carbon matrix; at the same time, the molybdenum disulfide and nickel oxide metal sites uniformly distributed in the micropores can serve as active centers for catalytic conversion, promoting the rapid conversion of intermediates, thereby achieving a higher sulfur utilization rate. The synergistic effect of the two avoids the formation and dissolution of polysulfide intermediates, and exhibits excellent specific capacity and cycle stability under high sulfur loading and low E / S conditions.
[0065] The above-described specific embodiments further illustrate the present invention in detail, but these descriptions cannot be understood as limiting the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a positive electrode for a lithium-sulfur battery with a composite solid phase conversion mechanism, characterized in that: The steps include: (1) mixing molybdenum salt, nickel salt and thiourea and dissolving them in water or ethanol to obtain a precursor solution; (2) placing carbon nanofibers in a precursor solution for hydrothermal treatment, taking out the treated carbon nanofibers, washing them with a cleaning agent and drying them to obtain a precursor; (3) calcining the precursor under a protective atmosphere at a temperature of 500 to 900° C. to obtain a lithium-sulfur battery positive electrode material with a solid phase conversion mechanism; (4) mixing the obtained solid phase conversion mechanism lithium-sulfur battery positive electrode material with sulfur powder to melt sulfur to obtain a sulfur positive electrode active material; (5) mixing the sulfur positive electrode active material, the conductive agent and the PVDF obtained in step (4) to form a slurry, coating the slurry on the current collector, and drying the slurry to obtain a lithium-sulfur battery positive electrode with a solid phase conversion mechanism; (6) The positive electrode, negative electrode, separator, spring sheet, gasket, positive and negative electrode shells and carbonate-based electrolyte of the lithium-sulfur battery with solid phase conversion mechanism obtained in step (5) are assembled into a lithium-sulfur battery, and the battery is initially cycled for 1 to 3 times to form a SEI film on the surface of the positive electrode to obtain a positive electrode of a lithium-sulfur battery with a composite solid phase conversion mechanism.
2. The method for preparing a positive electrode for a lithium-sulfur battery with a composite solid phase conversion mechanism according to claim 1, characterized in that: In the step (1), the molybdenum salt is ammonium molybdate or sodium molybdate, and the nickel salt is one of nickel chloride, nickel nitrate or nickel acetate; the molar concentration of the molybdenum salt in the precursor solution is 0.01 to 1 mol / L, the molar ratio of the molybdenum salt to the nickel salt is 1:1 to 50, and the molar ratio of the molybdenum salt to the thiourea is 1:3 to 10.
3. The method for preparing a positive electrode of a lithium-sulfur battery with a composite solid phase conversion mechanism according to claim 1, characterized in that: In the step (2), the hydrothermal treatment temperature is 150-300° C., and the time is 6-12 hours; the cleaning agent is water or ethanol; and the drying temperature is 60-80° C., and the time is 4-6 hours.
4. The method for preparing a positive electrode for a lithium-sulfur battery with a composite solid phase conversion mechanism according to claim 1, characterized in that: In the step (3), the protective atmosphere is nitrogen or argon, the heating rate is 2 to 5°C / min, and the calcination time is 3 to 6 hours.
5. The method for preparing a positive electrode for a lithium-sulfur battery with a composite solid phase conversion mechanism according to claim 1, characterized in that: In the step (4), the sulfur content in the sulfur positive electrode active material is 30 to 90 wt %, the temperature of the molten sulfur is 155 to 300° C., and the time is 8 to 12 hours.
6. The method for preparing a positive electrode for a lithium-sulfur battery with a composite solid phase conversion mechanism according to claim 1, characterized in that: In the step (5), the mass ratio of the sulfur positive electrode active material, the conductive agent and PVDF is 7-9:1-2:1, the conductive agent is one of Ketjen black, SuperP and acetylene black, and the coating thickness is 100 μm-300 μm.
7. The method for preparing a positive electrode for a lithium-sulfur battery with a composite solid phase conversion mechanism according to claim 1, characterized in that: In the step (6), the carbonate-based electrolyte is two of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, and propylene carbonate, with a volume ratio of 1-2:1-2; and the cycle voltage range is 0.01-1V.
8. The method for preparing a positive electrode for a lithium-sulfur battery with a composite solid phase conversion mechanism according to claim 1, characterized in that: In the step (6), the positive electrode component of the lithium-sulfur battery with a composite solid phase conversion mechanism mainly consists of a positive electrode material and a SEI membrane, wherein the positive electrode material is composed of a honeycomb microporous nano-chamber coated with carbon nanofibers formed by a combination of molybdenum disulfide and nickel oxide, the micropore diameter of the positive electrode material is 0.3 to 1 nm, the diameter of the carbon nanofiber is 2.0 to 5 μm, and the molybdenum disulfide is 10.7 to 78.3% of the mass of nickel oxide; the SEI membrane is composed of a combination of lithium polysulfide, a carbonate-based electrolyte and a composite.
9. An application of a lithium-sulfur battery positive electrode with a composite solid phase conversion mechanism obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The lithium-sulfur battery positive electrode of the composite solid-phase conversion mechanism is applied to the lithium-sulfur battery positive electrode.
Citation Information
Patent Citations
Solid-phase conversion sulfur positive electrode, preparation method thereof and lithium-sulfur battery
CN116936736A
Method for preparing lithium-sulfur battery positive electrode material from composite carbon nanofibers
CN113555543A
Solid-phase conversion mechanism sulfur-making positive electrode as well as preparation and application thereof
CN115732668A